Use of electronic resources by distance students in Nigeria: the case of the national open university, Lagos and Ibadan study centers (2013)
This study assessed factors affecting use of electronic information resources by distance learning students using the National Open University, Lagos and lbadan Study centers as a case study. Survey method was used for the study. The sampling method adopted for the purpose of this study was the simple random sampling techniques. The sampled respondents were drawn from the total population of 12,500 students at the Lagos and lbadan study centers. However 2% of the population from each study centers was used as the sample size. A structured questionnaire was developed and administered to elicit information from the respondents. A total of 250 copies of the questionnaire were retrieved, which is strictly administered to the students. Data collected were analyzed using simple descriptive statistics. The study revealed the various factors militating against the use of electronic information resources by the distance learning students. The result showed that the extent of use of electronic information resources was very low, coupled with the low level of awareness among the students. The result also showed that majority of the electronic information resources were not also in the centers. Based on these findings, the study outlines different measures that should be put in place by government to address the unavailability of most of the electronic information resources in the two different study centers.